The ekphrasis of arms in Alexandreide, or the facts of Alexander the Great (12th century) by Gautier de Châtillon - Cerdas Fallas, Maricela (2023)
The ekphrasis (evidentia, demonstratio) is a descriptive device that, since Antiquity, has been used as an exercise in rhetoric schools to provoke in the reader a vivid mental image of the represented reality. In Greek and Roman literature, the study of descriptions of an epic hero’s weapons has been of great importance; relevant examples are the shields of Achilles (Iliad) and of Aeneas (Aeneid). However, analysis of this descriptive device has been largely neglected in the Latin literature of the Middle Ages. This paper aims at contributing to fill this gap by analyzing the expressive functions of ekphrastic descriptions of weapons in the Alexandreis, a medieval epic poem in Latin by Gautier of Châtillon.